The nitric oxide synthase gene negatively regulates biofilm formation in Staphylococcus epidermidis - Wang, Jiaxue; Rao, Lulin; Huang, Zhuoan; Ma, Lili; Yang, Tian; Yu, Zhongqi; Sun, Aihua; Ge, Yumei (Frontiers in Cellular and Infection Microbiology, 2022)
Staphylococcus epidermidis (S. epidermidis) is one of clinically important conditioned pathogens, which can cause a troublesomely chronic implant-related infection once biofilm is formed. The nitric oxide synthase (NOS) gene, which is responsible for endogenous nitric oxide synthesis, has already been found in the genome of S. epidermidis, yet the specific mechanisms of which NOS has certain critical effects upon the pathogenicity in S. epidermidis are still unknown. The purpose of current study is to investigate whether NOS gene has an impact upon the biofilm formation in S. epidermidis. Firstly, the bioinformatics analysis of NOS gene was carried out, and homologous recombination was subsequently employed to delete this gene. The effects of NOS gene on biofilm formation of S. epidermidis and its underlying mechanisms were analyzed by bacterial growth assay, biofilm semi-quantitative determination, Triton X-100-induced autolysis assay, and bacterial biofilm dispersal assay. Additionally, the transcription level of fbe, aap, icaA, icaR and sigB that related to biofilm formation was also further investigated by qRT-PCR following NOS gene deletion. Bioinformatics analysis revealed that the NOS gene was conserved between the bacterial species which originate from different genera. The NOS gene deletion strain of S. epidermidis 1457 and its complementation counterpart were successfully constructed. Disruption of the NOS gene resulted in significantly enhanced biofilm formation, slightly retarded bacterial growth, remarkably declined autolysis rate, and drastically weakened bacterial biofilm dispersal. Our data also showed that fbe, aap and icaA genes were up-regulated significantly, but icaR and sigB genes displayed the opposite ending when compared with the wild strain. Therefore, these data strongly suggested that NOS gene can negatively regulate the biofilm formation in S. epidermidis by affecting the biofilm aggregation and dispersal.